Relationship between fasting glucose and retinopathy for diagnosis of diabetes: results from a population-based study in urban and rural China - Jonas, Jost B.; Xu, Liang; Xie, Xi Wei; Wang, Ya Xing (Retina, 2010)
Purpose: - The purpose of this study was to assess the relationship between the fasting plasma glucose cutoff of 7 mmol/L and the presence of retinopathy in a population in China. - Methods: - The Beijing Eye Study 2006 is a population-based study, which included 3,251 subjects aged ≥45 years. By using fundus photographs, retinopathy was assessed according to the Early Treatment of Diabetic Retinopathy Study. - Results: - The correlation between fasting plasma glucose concentration and retinopathy suggested a continuous relation instead of a uniform glycemic threshold for prevalent retinopathy. For the diabetes plasma glucose concentration cutoffs of 7.0 mmol/L, 5.6 mmol/L, and 7.8 mmol/L to differentiate between subjects with or without retinopathy, the sensitivities were 18.8%, 44.0%, and 15.4%, respectively, and the specificities were 94.3%, 73.8%, and 96.6%, respectively. After excluding subjects with known diabetes and/or subjects on antidiabetic treatment, the sensitivities of diabetes plasma glucose concentration cutoffs of 7.0 mmol/L, 5.6 mmol/L, and 7.8 mmol/L to differentiate between subjects with or without retinopathy were 7.9%, 34.2%, and 6.3%, respectively, and the specificities were 96.5%, 77.1%, and 98.1%, respectively. - Conclusion: - Confirming a recent study from Australian and North American populations, the results suggest that also for the Chinese population, a uniform glycemic threshold for prevalent retinopathy does not exist.
Gesehen am 14.09.2023